Ice kool / Varyllyna Cassandra Uyah Darrell … [et.al.]. - Darrell, Varyllyna Cassandra Uyah; Abdul Nassir, Azizah; Stephen Lamkop, Rejina; Wan Ismail, Sharifah Siti Nurlaila; Anthony, Andlyn Lisa (2014)
ICEKOOL (ICE DISTRIBUTORS) is full-service ice distributor dedicated to consistently providing high customer satisfaction by rendering excellent services, quality products and furnishing an enjoyable atmosphere at an acceptable price and value relationship. We also maintain a friendly, fair and creative work environment, which respects diversity, ideas and hard work.